Estimation of the ruin probability of an insurance company operating on a BS-market - Androshchuk, M. O.; Mishura, Yu. S.; Андрощук, М. О.; Мішура, Ю. С. (Institute of Mathematics, NAS of Ukraine, 2007)
We obtain an estimate for the ruin probability of an insurance company that invests a part of its capital in stocks and puts the rest of the capital in a bank account. An insurance premium is established depending on the capital of the insurance company.